2022
DOI: 10.1111/ijfs.15542
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, and characterization of the globulin from wheat germ

Abstract: This research optimized the extraction and purification of globulin from wheat germ and assessed the molecular weight distribution and structure properties of the globulin obtained. The results showed that the relative extraction efficiency and purity of wheat germ globulin (WGG) reached 18.0% and 89.1% under the enzymolysis conditions of 0.32& a-amylase, pH 6.5, and 55 °C. The maximal precipitation rate of WGG (91.3%) was obtained with pH 4.3 (acid precipitation). Additionally, the molecular weight of WGG was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…To extend this storage time, it seems expedient to isolate the protein from wheat germ. It has been reported that it is possible to obtain protein isolate from wheat germ at a yield of over 90% (Fan et al, 2022; Hettiarachchy et al, 1996), which can make it possible to increase the content of this macronutrient in final products.…”
Section: Introductionmentioning
confidence: 99%
“…To extend this storage time, it seems expedient to isolate the protein from wheat germ. It has been reported that it is possible to obtain protein isolate from wheat germ at a yield of over 90% (Fan et al, 2022; Hettiarachchy et al, 1996), which can make it possible to increase the content of this macronutrient in final products.…”
Section: Introductionmentioning
confidence: 99%